Proposing a training program to develop the special flexibility of students in in the floor skills gymnastics - بن شهرة محمد ياسين,; Ziouch ahmed, (sports creativity, 2025)
The study aimed to propose a training program to develop the special flexibility of students in the floor skills gymnastics in " Institute of Science and Technology of physical and sports activities at the University of Zian Ashour Djelfa". In his study, the researcher adopted the experimental approach in the design of the one group and the tribal and remote standards. Four physical tests were used to measure flexibility. The researcher reached the following results: -The results of the study showed that there were statistically significant differences between the pre-test and the post-test of the sample of the research in favor of the post-test in the tests of special flexibility of students in gymnastics floor skills. - The study showed that the proposed training program has a positive effect on the development of the special flexibility of the research sample, with a significant increase in all the tests of flexibility.